The Durability of Phenol-Resorcinol Formaldehyde Glue Joints on Three Malaysian Hardwood Species - Sahri, Mohd Hamami (1990)
The integrity and durabilily of phenol-resorcinol fOrmaldehyde glue joints on three Malaysian hardwood species were evaluated. Single and mixed-species laminations were produced using phenol-resorcinol formaldehyde adhesive at room temperature. The integrity of the glue bond to delamination was lested according to the ASTM D 1101-59 specification. All combinations, produced very low delemination percentage levels and met the requirement specified by AlTC. The highest delamination percentage was shown by Kempas-Kempas combination with only 4.7% and the lowest was Seraya - seraya combination with 0.0% delamination. Mixed-species combinations offered lower percentage of delamination that their single-species counterparts.